Relationship between disease and disease severity and semaphorin 5A and hemogram level in obsessive–compulsive disorder. (1st October 2021) - Karatas, Kader Semra; Bahceci, Ilkay; Telatar, Tahsin Gokhan; Bahceci, Bulent; Hocaoglu, Cicek
Abstract: Objective: Semaphorin 5A (SEMA 5A) is a neuroprotein that regulates the formation of excitatory synapses between neurons, important in autoimmunity, inflammatory processes and behaviors. This study aimed to investigate the SEMA 5A levels in patients with obsessive–compulsive disorder (OCD) diagnosed for the first time and evaluate the relationship of disease and disease severity with the blood SEMA 5A level and hemogram. Methods: More than 41, 465 patients who applied to the psychiatry clinic from January 2018 to December 2020 were evaluated according to the DSM-5 criteria; 57 patients diagnosed with OCD for the first time, who met the inclusion criteria, were included in the study. Disease severity was investigated administering the Yale Brown Obsessive Compulsion Scale. The peripheral blood SEMA 5A level and hemogram were measured and evaluated in relation to platelet (PLT) activity, neutrophil–lymphocyte ratio (NLR), PLT–lymphocyte ratio (PLR), monocyte–lymphocyte ratio (MLR), C-reactive protein (CRP), and compared with control group of 26 people. Results: The comparison of the groups revealed a significant difference in SEMA 5A and CRP level, neutrophil count and percentage, lymphocyte count, PLT activity. A significant correlation was found between disease and SEMA 5A level, NLR, PLR, and PLT parameters in diagnosis of OCD. As the severity of OCD increased, the SEMA 5A level and PLT count decreased, while the PDW and MLR values increased. Conclusion: In patients with OCD, a relationship was found between plasma SEMA 5A, PLT activity, NLR, PLR, and MLR activity levels with disease and the disease severity.